Evaluation of the Application of Blended Learning in PAI Subjects at SMAN 1 Prambon, Nganjuk - Iskandar Tsani; Cicik Erikawati; Sufirmansyah Sufirmansyah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This article aims to evaluate the application of blended learning in the eyes of Islamic Education at SMA Negeri 1 Prambon, Nganjuk. This article is prepared based on qualitative approach field research with the type of evaluative research. Researchers use Stufflebeam's CIPP theory which includes aspects of context, input, process, and product. Data was collected through interviews, observation, documentation, and questionnaires. Then, the data is analyzed interactively as Miles-Huberman theory, which includes data collection, data reduction, data display, and conclusions. This article concludes: 1) Context: the application of blended learning is designed by the school to provide reinforcement to students after previously learning was carried out fully online. 2) Inputs: schools provide adequate infrastructure, encourage collaboration between teachers and computer laboratory operators in managing blended learning, and allocate funding proportionally from the government to each student. 3) Process: face-to-face learning is used as a reinforcement of online learning (via Youtube) that has been implemented. Attendance is done through the school website. Formative assessment is carried out through google form. Learning montoring is carried out online and periodically to minimize obstacles in learning, such as student attendance, IT mastery, internet connection, and device storage. 4) Product: assessment of learning outcomes on students' spiritual attitudes, social attitudes, knowledge, and skills is carried out through questionnaires. In general, student learning outcomes fall into the good category in all aspects.